The home management of Artificial Nutrition: a survey among doctors and nurses - Gamberi, Sara; Calamassi, Diletta; Coletta, David; Dolenti, Silvia; Valoriani, Alice; Tarquini, Roberto (Acta Biomedica Atenei Parmensis, 2017)
Abstract. Background and aim of the work: The management of Artificial Nutrition (NA), especially in the home environment (HAN) requires specific skills in order to ensure the correct therapeutic education, prevention of complications and the provision of appropriate treatment to the person. The aim of this survey was to identify the perceptions of nurses and doctors, as well as comparing to their perceived competence in NA and the gap between their perceived versus actual knowledge and management methods. Methods: This observational study was conducted in a Tuscan health region of Italy, involving 50 Home Care Services nurses and 50 general practitioners. Participants were asked to complete an online questionnaire that was constructed for purpose. Results: The results show that for the management of the person with NA, both for doctors and for nurses show great variability in responses. Less than half of those providing care make assessments of nutritional status and dysphagia as well as the possibility of re-feeding by natural means in NA patients. Care providers expressed uncertainty as to which professional should carry out such assessments. A mismatch was also evident between the skills possessed and the self-assessments performed regarding their knowledge base of NA. Almost all of doctors of nurses indicated a desire to participate in training events relating to NA. Conclusions: The results highlight the need for caregivers to have specific operating protocols. The results also highlight the need to aim to work as a team, emphasizing the importance of basic communication as well as the need for clarity as to the responsibilities and roles of the professionals involved. Key words: Artificial Nutrition, Nurses, Doctors, home management, skills, training, team